A method to provide magnet-free long straight sections in low-emittance synchrotron radiation sources - Tanaka, H (Journal of synchrotron radiation, 1997)
In a low-emittance synchrotron radiation source it is difficult to provide magnet-free long straight sections (MLSSs) a few tens of metres long because introducing MLSSs to the radiation source causes symmetry breaking and markedly reduces dynamic stability. To overcome this difficulty and realize MLSSs in such a ring, a method of building MLSSs is proposed starting from the stable lattice with high symmetry and proceeding via a transient lattice